2021
DOI: 10.1016/j.smim.2021.101508
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of immune response in COVID-19: Exploring dysregulation and exhaustion

Abstract: One and half year following the occurrence of COVID-19 pandemic, significant efforts from laboratories all over the world generated a huge amount of data describing the prototypical features of immunity in the course of SARS-CoV-2 infection. In this Review, we rationalize and organize the main observations, trying to define a “core” signature of immunity in COVID-19. We identified six hallmarks describing the main alterations occurring in the early infection phase and in the course of the disease, which predis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 250 publications
(385 reference statements)
1
37
0
3
Order By: Relevance
“…This is in agreement with recently published ex vivo studies that found a higher NK cell activation status in severe than in mild COVID-19, which was hallmarked by the high-level expression of perforin and evidenced a status of NK cell exhaustion. 9 , 17 Another ex vivo study analyzed the potential of peripheral blood mononuclear cells derived from patients with COVID-19 to induce an ADCC response against rituximab-coated Raji cells. 18 The authors found a considerably defective ADCC response in hospitalized patients with COVID-19, which also shows exhaustion of ADCC mediating cells in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with recently published ex vivo studies that found a higher NK cell activation status in severe than in mild COVID-19, which was hallmarked by the high-level expression of perforin and evidenced a status of NK cell exhaustion. 9 , 17 Another ex vivo study analyzed the potential of peripheral blood mononuclear cells derived from patients with COVID-19 to induce an ADCC response against rituximab-coated Raji cells. 18 The authors found a considerably defective ADCC response in hospitalized patients with COVID-19, which also shows exhaustion of ADCC mediating cells in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hematological analysis of COVID-19 patients has been reported to show lymphopenia, which is an important indicator of severe SARS-CoV-2 infection and poor prognosis ( 76 78 ), suggesting a defect in their adaptive immune system. Multiple sets of clinical data show that the absolute number of circulating lymphocytes is significantly lower in COVID-19 patients in the ICU than in patients with mild to moderate infection ( 79 ). However, the immune mechanism in COVID-19 patients is complex and still unclear, especially about potentially orchestrated acute mortality.…”
Section: Immune Systemmentioning
confidence: 99%
“…However, the absolute number of peripheral circulating T cells was significantly reduced in COVID-19 patients, which may be because of increased lymphocytosis locally recruited to lung tissue or increased lymphocyte adhesion to the endothelium ( 84 ). Moreover, elevated levels of cytokines IL-6, IL-10, and TNF-α were observed in severe COVID-19 patients, directly affecting T-cell subsets and indirectly affecting dendritic cells and neutrophils, thereby reducing lymphocyte count ( 79 , 85 ).…”
Section: Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations